Dietary supplements : a framework for evaluating safety (Online access: NCBI NCBI Bookshelf., 2005)
"The sale of supplements has been steadily increasing - all together, the various types of dietary supplements now bring in more than $18 million a year. Given these factors, what kind of information can the Food and Drug Administration use to effectively regulate dietary supplements? Dietary Supplements: A Framework for Evaluating Safety provides an outline for evaluating dietary supplement safety and protecting the health of consumers."--Jacket